Research on Social and Environmental Accounting: Current Trends and Future Approaches - Bipasha Saha; Anup Kumar Saha; Mahnoor Khan (Indonesian Journal of Sustainability Accounting and Management, 2019)
Climate change has attracted public awareness in recent years, which, in turn, has created potential opportunities and concerns for business. This paper examines the manner in which empirical studies on social and environmental accounting (SEA) disclosures have contributed to the existing knowledge. It combines theoretical and practical approaches to SEA to provide researchers with creative and holistic access to the knowledge. The study finds the literature on SEA to be far-reaching, flourishing, and employing exciting and diverse statistical methodologies to measure relevant disclosures. It goes on to analyze the theories, motivations, prior literature, and methodologies employed in international SEA literature. The present study contributes to the crafting of a systematic overview of the literature on SEA and opens up potential avenues for research in this discipline by combining current trends in theoretical and practical approaches to SEA research.